ON THE CONCEPT OF SUCCESS OF PUBLIC ADMINISTRATION ACTIVITIES (Coordinates of Public Administration, 2026)
The article provides a theoretical interpretation of success of public administration activities as a complex and multidimensional category, which is gaining popularity in foreign public administration. The purpose of the article is to clarify the concept of success of public administration activities by analysing contemporary approaches to its understanding, and to identify its main factors. In public administration, the concept of success remains underdeveloped and is seldom used to talk about achieving goals and results in administrative activity. The concepts of «success», «quality», «efficiency», and «effectiveness» in public administration are compared, and it is shown that the concept of success has a broader meaning, since it encompasses not only the achievement of goals, but also the social significance of the result, legitimacy, support, trust, and the ability to maintain a positive effect over time. The main theoretical approaches to the interpretation of success are generalised, in particular through the prism of classical philosophical ideas and modern public policy concepts: A. McConnell’s approach to the dimensions of success, M. Moore’s concept of public value, and the ideas of positive public administration. It is shown that success of public administration activities cannot be reduced solely to quantitatively measurable indicators or the formal achievement of stated goals. It should be considered in procedural, programmatic, political and endurance dimensions in order to identify where exactly successful performance produces the best result. Particular attention is paid to the factors of success, namely: the quality of managerial activity, coherence of goals, fairness of evaluation, staff motivation, and institutional capacity. It is concluded that the success of public administration should be interpreted as an integral category that combines objective and subjective evaluation parameters and reflects the real ability of public authorities to act in the interests of the individual, society, and the state.